THE RELATIONSHIP OF PREGNANT WOMEN'S KNOWLEDGE WITH ANXIETY IN FACING LABOR DURING THE COVID-19 PANDEMIC - Ni Made - Darmiyanti; Vivin Frida Oktaviani (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Most people believe that the initial story of the spread of the corona virus or coronavirus disease 2019 abbreviated as Covid-19 began at the end of 2019 when someone contracted the corona virus from animals traded at the Huanan seafood market, Wuhan city, Hubei province, China, and spread to other countries. The purpose of this study was to find out whether there is a relationship between knowledge of pregnant women about Covid-19 and the level of anxiety of pregnant women in facing childbirth during the Covid-19 pandemic in Manggis Village, Bali in 2020.Methods: This research design uses the correlation method. This study collect the dataa from the third trimester of pregnant women with a population of 63 people and samples that meet the inclusion criteria was 27 people in Manggis Village, Bali in 2020.Result: The results showed that there was a significant relationship between the knowledge of pregnant women about Covid-19 with the level of anxiety of pregnant women in facing childbirth during the Covid-19 pandemic with a sig. <0.05 with a strength level of 0.838, which means that the relationship is very strong and the relationship is unidirectional. In the statistical test with the Spearman rank, the results showed that there was a significant relationship between knowledge of pregnant women about Covid-19 and the level of anxiety of pregnant women in facing childbirth during the Covid-19 pandemic with a value of sig. <0.05 with a relationship strength level of 0.838 which means the relationship very strong and the relationship is unidirectional.Conclusion: Thus, it can be interpreted that if knowledge is increased, anxiety will decrease